Exploring Youth Participation in Food Production through Smart Agriculture: The Cool Factor - P. T. Mburu; T. Maswabi (Journal of Management Research, 2024)
Africa has highest percentage of arable land and high percentage of its total population is a youthful population, yet it is faced with food deficit. At the same time Africa’s unemployment records an all-time high. This disconnect point to underutilization of one or more factors of production to facilitate food security, This paper explores various ways in which youth can be engaged in food production by changing the perception of agriculture to be a cool profitable career engagement thus increasing food security and employment. The engagement by the youth in agriculture need not be perceived in the traditional farming but an involved in all aspects of food security chain. This can be achieved through engaging the youth in the development and application of modern technology especially in ICT, focused on food production chain.